Dinamika Sosial Pembangunan Masyarakat Era Generasi Emas di Indonesia - Putri, Aan Iminullah Eka (TarbiyahMU, 2025)
This article discusses the social dynamics of community development in Indonesia's golden generation era. The Indonesian nation has Pancasila as its ideology, which is rooted in the inherent values of the Indonesian people. The social dynamics of community development during the Golden Generation era are also influenced by cultural contexts and local values. Indonesia is a country rich in cultural diversity, and factors such as religion, customs, and local wisdom play a significant role in shaping social patterns and community development. The golden generation is an era that coincides with historical and temporal changes, and the social groups that form this era have distinctive characteristics that can become unique traits. A generation must be prepared to face the challenges of its time, achieve development with existing and future resources, and maintain the sustainability of development and those resources. If a generation is linked to development, then the formation of the golden generation is inseparable from education, as the existence of a generation is inseparable from the nature, characteristics of the population, and the state of the nation. The generations that will play a role in the upcoming golden generation are Generation Y and Generation Z, who will carry forward the nation's legacy.